Comparative Assessment of Archaeological Scene Reconstruction Using Iphone LIDAR Scanner - Bhatta, Binod Prasad; Shah, Abishek; Kumari Chaulagain, Man; Dhungana, Aagya; Mandal, Lalit; Koirala, Punam; Thapa, Shangharsha; Shankar Panday, Uma (Journal on Geoinformatics, Nepal, 2025)
Archaeological sites hold immense economic value for Nepal, contributing to income and overall economic growth. These sites are susceptible to damage from both human activities and natural factors, needing swift and cost-effective reconstruction efforts. In addressing this challenge, 3D scene reconstruction emerges as a crucial reverse engineering method. Various techniques, such as LiDAR and Photogrammetry, are used for this purpose. While LiDAR offers precise models, its high cost has limited its accessibility. A notable development in this context has been achieved due to the introduction of consumer-grade LiDAR sensors, particularly with the integration of such sensors into iPhones. The primary focus of this research revolves around assessing the efficacy of consumer-grade LiDAR sensors in archaeological scene reconstruction. Utilizing the SiteScape and 3D Scanner apps, several tests with various settings were conducted to generate point clouds of the studied archaeological structures. The obtained point clouds were analyzed to assess point density variations across various application settings. Meshes were generated from these point clouds and the measurements were then taken from digital meshes which are compared with in-situ measurements, allowing for the calculation of relative error. Measurements obtained through SiteScape displayed a maximum difference of 4.17% and a minimum difference of 0.05%. In contrast, the 3D Scanner exhibited a maximum difference of 6.22% and a minimum difference of 0.09%. The findings suggest that the SiteScape app provides a higher point density and a higher accuracy than the 3D Scanner.